(untitled) - McMahon, Edward R. (Bloomfield, 2006)
In recent years, a "democratic entitlement" doctrine, in which citizens have a universal right to be governed according to democratic standards, has begun to take form in international law. Acceptance of this doctrine is widely, but not fully, shared throughout the world. Developing a global consensus on democratic entitlement has been, and continues to be, a daunting task. While domestic factors will always play a significant role, regional organizations are also shaping the adoption of democracy.
Keywords: International agencies,International relations,Democracy,Chi nhánh quốc tế